«The cinema spectator is a passive being»: António Ferro, education through cinema, censorship and propaganda in Portugal, 1917-1949 - Fernandes Paz, Ana Luísa; Ramos do Ó , Jorge (Historia y Memoria de la Educación, 2022)
This article seeks to understand the use of cinema as an educational device during the Estado Novo regime, particularly with regard to newsreels. Weundertake a genealogical approach to our research, seeking to reconstitute the provenance of the newsreels within the framework of António Ferro’s Politics of the Spirit. To this end, the article focuses on two documentary series: the legislation produced on cinema, in which the authorities recognize its educational character; and the work of António Ferro himself, writer and publicist responsible for the National Propaganda Secretariat, created in 1933 and made National Information Secretariat in 1944.